Ecotoxicological thresholds—practical application to an industrial inventory. (9th March 2015) - Gutsell, Steve; Hodges, Geoff; Marshall, Stuart; Roberts, Jayne
Abstract: The concept of thresholds of toxicological concern as a potentially useful tool in environmental risk assessment has been applied to the inventory of a home and personal care products company to derive a series of chemical class–based ecotoxicological threshold of concern (ecoTTC) values. Cationic chemicals of various types show notably higher toxicity than other classes and should be treated separately. Despite this, the ecoTTC for the full data set in the present study is only slightly lower than that derived previously for chemicals causing toxicity via Verhaar modes of action (MoAs) 1 to 3. Exclusion of cationic chemicals resulted in an ecoTTC value slightly higher than the MoA 1 to 3 value. These observations indicate that such data sets contain few specifically acting chemicals. The applicability of threshold approaches in environmental risk assessment has been extended to include a limited number of inorganic/organometallic chemicals, polymers, and all classes of surfactants. The use of such ecoTTC values in conjunction with mode of action–based quantitative structure–activity relationships will allow the efficient screening and prioritization of large inventories of heterogeneous chemicals, focusing resources on those chemicals that require additional information to better understand any potential risk. Environ Toxicol Chem 2015;34:935–942. © 2015 SETAC